Plant food-derived antioxidant nutrients in neuroprotection against chemotherapy-induced neurotoxicity: from molecular mechanisms to clinical applications - Li, Weizhong; Yang, Dan; Zhang, Zihan; Wang, Meizi; Xu, Senlei; Jiang, Ruiyang; Chen, Jin; Wu, Chaokui; Qian, Jun (Frontiers in Nutrition, 2025)
Chemotherapy-induced peripheral neuropathy (CIPN) is one of the most challenging dose-limiting toxicities in contemporary oncology, affecting 19–85% of patients receiving neurotoxic chemotherapy agents. The pathophysiological mechanisms of CIPN are complex, involving multiple interconnected processes including oxidative stress, neuroinflammation, neurotrophic factor depletion, and mitochondrial dysfunction. Plant-derived antioxidant nutrients have emerged as promising candidates for CIPN prevention due to their unique multi-target neuroprotective capabilities. This comprehensive review systematically analyzes the molecular protective mechanisms of plant-derived nutrients, evaluates existing clinical evidence, and discusses practical application strategies. The focus is on the neuroprotective effects of curcumin, green tea catechins, vitamin E, and other plant compounds. Evidence indicates that these compounds exert protective effects through activation of endogenous antioxidant systems, modulation of inflammatory pathways, enhancement of neurotrophic factors, and protection of mitochondrial function. While clinical evidence is still accumulating, preliminary studies show encouraging results, providing a scientific basis for developing plant food-based CIPN prevention strategies.